Biomechanical adjustments of the basketball jump shot erformed over differently high opponents - Kambic, T.; Stepišnik Krašovec, F.; Erculj, F.; Štirn, I. (Journal of Human Kinetics, 2022)
Biomechanical adjustments of the jump shot in presence of an opponent and their associations with shooting efficiency remain to be determined in elite basketball. The aim of this research was to examine the selected biomechanical determinants of the jump shot when shooting over opponents of different height. Nineteen elite basketball players, age 22 ± 3 years, performed three trials of 20 basketball shots in a crossover, randomised manner: over an obstacle of the height of standing reach (RH), over reach height with additional 20 cm (RH+20 cm), over reach height with additional 40 cm (RH+40 cm), and the maximum height jump shot without an obstacle (JSmax). Jump height, the ball entry angle, and shooting efficiency were measured on each trial. Jump height when shooting over RH+40 cm was significantly higher than RH+20 cm (+0.022 m, p = 0.30) and RH (+0.023 m, p = 0.029). Similarly, the ball entry angle was greater at RH+40 cm compared to RH (+7.19 °, p < 0.001) and RH+20 cm (+2.90°, p < 0.001). In contrast, shooting efficiency decreased significantly when shooting over RH+40 cm compared to RH (-10.79%, p = 0.048) and RH+20 cm (-8.95%, p = 0.015). We recorded the highest jump height (0.35 ± 0.08m, p < 0.001) and the lowest angle of entry (39.16 ± 1.19°, p < 0.001) when participants performed JSmax. Shooting over higher opponents should be prioritised in training to significantly improve shooting efficiency. Future research is needed to determine additional potential biomechanical determinants of a successful jump shot in elite basketball.